2002
DOI: 10.1016/s0014-5793(02)03862-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of EGF receptor autophosphorylation by α‐hemolysin of Staphylococcus aureus via protein tyrosine phosphatase

Abstract: In the presence of assembled K K-hemolysin (K K-HL) of Staphylococcus aureus, the epidermal growth factor receptor (EGFr) is rapidly dephosphorylated. Several obvious possibilities that otherwise would have contributed to the dephosphorylation were ruled out. Instead, an elevation in the activity of a protein tyrosine phosphatase appears to be responsible for the observed loss of phosphorylation signal of EGFr. For this dephosphorylation, the assembly of K K-HL is necessary while lytic pore formation is not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
4
1
Order By: Relevance
“…However, both p‐Tyr‐EGFR‐specific sandwich enzyme‐linked immunosorbant assay (ELISA) and immunoprecipitation with EGFR‐specific antibodies followed by Western blots with conventional phosphotyrosine‐specific antibodies failed to detect EGFR tyrosine phosphorylation in toxin‐treated cells (not shown). This was in accord with a previous report in which EGFR tyrosine phosphorylation was investigated in α‐toxin‐treated A431 cells (Vandana et al ., 2003). However, Western blot experiments with an antibody that specifically recognizes phosphotyrosine 1173 of the EGFR revealed that the receptor becomes phosphorylated at this site in toxin‐treated cells (Fig.…”
Section: Resultscontrasting
confidence: 56%
“…However, both p‐Tyr‐EGFR‐specific sandwich enzyme‐linked immunosorbant assay (ELISA) and immunoprecipitation with EGFR‐specific antibodies followed by Western blots with conventional phosphotyrosine‐specific antibodies failed to detect EGFR tyrosine phosphorylation in toxin‐treated cells (not shown). This was in accord with a previous report in which EGFR tyrosine phosphorylation was investigated in α‐toxin‐treated A431 cells (Vandana et al ., 2003). However, Western blot experiments with an antibody that specifically recognizes phosphotyrosine 1173 of the EGFR revealed that the receptor becomes phosphorylated at this site in toxin‐treated cells (Fig.…”
Section: Resultscontrasting
confidence: 56%
“…The proteins were transferred to a nitrocellulose membrane using 10 mM 3-[cyclohexylamino]-1-propanesulfonic acid buffer (pH 10.5) at 150 mA for 2 h. The blot was subjected to immunodetection with antiphosphotyrosine antibody. The cells treated with TGF␣ exhibited a slightly diffuse EGFr band because of their phosphorylation (Vandana et al 2003).…”
Section: Phosphorylation Of Egfr Erk P38 and Caveolin-1mentioning
confidence: 99%
“…We have carried out the present study with the help of H35N mutant of α-HL, an oligomerization deficient mutant of the toxin. The H35N does not assemble beyond the membrane bound monomeric stage on target cells as it cannot form efficient inter-protomer interactions to form a pre-pore [8]. Earlier studies have shown that low doses of α-HL treatment of Jurkat T cells resulted in caspase activation via mitochondrial pathway and oligonucleosomal DNA fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…H35N) was constructed as described earlier [6]. α-HL and H35N were cloned and expressed in E. coli JM109(DE3) under the control of T7 promoter and purified as described earlier [7], [8].…”
Section: Methodsmentioning
confidence: 99%